ANALISIS STRATEGI KAMPANYE PUBLIC RELATION RATU DEWA DI INSTAGRAM DALAM MEMBANGUN PERSONAL BRANDING BERBASIS KONTEN - Selvi Musleni; Puspa Wijayanti; Fitriyani; Marselah; Sri Hertimi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This study aims to analyze Ratu Dewa's public relations campaign strategy on Instagram in building content-based personal branding. The study used a qualitative approach with a content analysis method on the Instagram account @ratudewa posts. The analysis was conducted through two theoretical frameworks, namely the Four-Step PR Process model and Peter Montoya's personal branding theory. The results show that Ratu Dewa utilizes various types of content in the form of government, social, religious, and personal activities that are arranged in a planned manner with strong visuals and storytelling narratives in the captions. This study concludes that structured and emotionally close-based Instagram content management has proven effective as a public relations campaign instrument in building the personal branding of public figures in the digital era.